Initial Returns and Long-Term Performance of IPOs in China 2001–2011. Evidence on the Influence of the Institutional and Economic Context from the Shanghai Stock Exchange - Christoph J. Börner; Phil Pezus (Credit and Capital Markets – Kredit und Kapital, 2015)
In this article, we analyze initial public offerings on the Shanghai Stock Exchange (SSE) from 2001 to 2011 to investigate underpricing and long-term performance in the Chinese IPO market. Multi-linear OLS regressions are applied to 332 IPOs of A-shares for which the necessary data were extracted from the SSE factbooks and other sources. We analyze the overall sample as well as two sub-samples. Initially, we test whether the massive underpricing reported in previous studies continued in the years after reforms were implemented in China. In our sample, we observe an initial return of 93.42 %, on average. Although this value seems very high compared to Western markets, it is relatively low compared to those reported in previous studies of the Chinese IPO market. Moreover, under-pricing decreased over the years. To obtain a deeper understanding of the Chinese IPO market we look for explanatory variables which can explain initial returns. Our regression analyses reveal that the issuers" size, the lottery success rate, and the date of the IPO are significant variables for explaining initial returns. All in all, these findings are in line with previous literature affirming the emerging state of the market, although interestingly, we do not observe a significant link between the underwriters" reputation, the issuers" industry, the lock-up period and the initial return. We consider these results as an indication that the market has gained in balancing issuers" and investors" interests. This conclusion is supported by the observation of a high but decreasing degree of long-term underperformance of the IPOs. In summary, the Chinese IPO market seems to have developed in recent years but remains in an emerging state. Further development depends on political willingness to improve the market-orientation of the capital markets. – – Initial Returns und langfristige Rendite von Börsengängen in China 2001–2011. Ergebnisse zum Einfluss des institutionellen und wirtschaftlichen Kontext von der Börse in Shanghai In dem vorliegenden Beitrag werden Börsengänge an der Börse in Shangai in den Jahren 2001–2011 untersucht, um Underpricing und langfristige Rendite am Chinesischen IPO-Markt zu analysieren. Mit Hilfe eines multilinearen Regressionsmodells werden 332 Börsengänge betrachtet. Es erfolgt sowohl die Analyse des Gesamtsamples als auch zweier Subsamples. Als erstes Ergebnis lässt sich ein durchschnittlicher Initial Return von 93,42 % festhalten, das damit zwar im internationalen Vergleich hoch, im Vergleich zu älteren Studien für China jedoch niedrig ausfällt. Ferner nimmt das Underpricing über den Betrachtungszeitraum hinweg ab. Bezogen auf die Erklärungsfaktoren erweisen sich das Emissionsvolumen, die Zuteilungsquote ("Lottery Success Rate") und der Zeitpunkt der Emission als durchgängig signifikant. Diese Ergebnisse bestätigen frühere Befunde in der Literatur und belegen, dass der IPO-Markt in China noch in der Entwicklung steht. Die Reputation des Underwriters, die Branche des Emittenten sowie die Lock-up-Periode als nicht signifikant, was darauf hindeutet, dass der Markt zunehmend in der Lage ist, den Interessenausgleich zwischen Emittenten und Investoren zu bewirken. Dies wird dadurch bestätigt, dass die langfristige Performance der Emission zwar deutlich negativ ist, sich im Zeitablauf aber verbessert hat. Insgesamt zeigt sich, dass der IPO-Markt in Shanghai sich zwar fortentwickelt hat, aber immer noch in einer Entwicklungsphase steht. Die weitere Entwicklung wird stark auch vom politischen Willen zu einer marktwirtschaftlichen Öffnung des Kapitalmarktes abhängen.
Keywords: G12; 330; Initial Public Offering (IPO); Underpricing; Initial Returns; China